Innovation in general education governance towards the school autonomy model: International experiences and implication lessons for Vietnam’s education - Huong, Nguyen Thi; Pham, Phuong Thu (International Journal of Psychosocial Rehabilitation, 2020)
Innovation in general education governance is one of the development trends not only in Vietnam but also in the world. This is also an important measure to change and improve the quality of education, especially expand autonomy of high schools and universities. The paper focuses on some main contents: overview of general education; the experiences of some countries in the implementation of the school administration model towards the school autonomy model so that give lessons for Vietnam’s education can be learned in the context of development conditions nowadays. The results in this work would be used to classify the schools into the various groups. The data also analysts on decision-making capability, on what we called an “index of school autonomy”, expressed the possible level of school-level decision-making.